2021
DOI: 10.1021/acsami.0c21883
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Functional Template-Induced In Situ Polymerization Process Enables the Hierarchical Carbonaceous Nanotubes with Simultaneous Sn Cluster Incorporation and Nitrogen-Doping for Superior Potassium-Ion Storage

Abstract: Potassium ion-based energy storage devices have received extensive attention for grid-level applications due to their abundant natural resources and low cost. However, the large ionic radius of K + leads to inferior capacities and cyclic stability, which hinders their practical application. Herein, hierarchical carbonaceous nanotubes with simultaneous ultrasmall Sn cluster incorporation and nitrogen doping (denoted as u-Sn@NCNTs) are fabricated using MnO 2 nanowires as a dual-functional template (in situ polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Potassium-ion batteries (PIBs) are regarded as one of the most promising candidates to lithium-ion batteries (LIBs) for large-scale energy storage owing to the abundant resource, greater accessibility, and less cost. Simultaneously, it has been suggested that potassium has a standard redox potential (−2.94 V) similar to that of lithium (−3.04 V). However, the orthodox anode materials for LIBs are unbefitting for PIBs due to the inevitable issues induced by the larger ionic radius of K + (1.38 Å), such as the sluggish transport kinetics in the electrode materials and the fragile structures, impeding the mass production of PIBs. In order to fulfill the requirements of practical application, it is necessary to find suitable electrode materials for PIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium-ion batteries (PIBs) are regarded as one of the most promising candidates to lithium-ion batteries (LIBs) for large-scale energy storage owing to the abundant resource, greater accessibility, and less cost. Simultaneously, it has been suggested that potassium has a standard redox potential (−2.94 V) similar to that of lithium (−3.04 V). However, the orthodox anode materials for LIBs are unbefitting for PIBs due to the inevitable issues induced by the larger ionic radius of K + (1.38 Å), such as the sluggish transport kinetics in the electrode materials and the fragile structures, impeding the mass production of PIBs. In order to fulfill the requirements of practical application, it is necessary to find suitable electrode materials for PIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the feasibility of the MoSe 2 ⊂CNB electrode, a KIHC device composed of an MoSe 2 ⊂CNB anode and a commercial AC cathode is assembled (Figure A). Upon charging, K + is inserted into the MoSe 2 ⊂CNB anode, while KFSI – is absorbed on the surface of the AC cathode . Then, during the discharge process, the reaction experiences an opposite process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Electroactive Sn, together with the heteroatom doping of carbonaceous materials, is expected to further enhance the electrochemical properties. Li et al 150 designed a Sn cluster@NC tube via a template-induced in situ polymerization process, which exhibited high cycling stability with 149.9 mAh g −1 at 1 A g −1 after 4000 cycles. Very recently, Ju et al 151 reported Sn@rGO as an anode, which was fabricated via freeze-drying and calcination.…”
Section: Battery-type Anode Materialsmentioning
confidence: 99%